THE USE OF THINK-PAIR-SHARE TECHNIQUE TO IMPROVE THE WRITING ABILITY OF THE STUDENTS OF SMA NEGERI 03 PEKANBARU IN RECOUNT TEXT - Muhammad Ariansyah; Fadly Azhar; Masyhur ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aimof this research was to know whether or not Think-Pair-Share technique could improve students’ ability in writing recount texts and how it could improve the ability. Classroom action research was conducted in two cycles to 34 students of X-2Class of SMAN 03 Pekanbaru as the participant of this research. The data were collected through written test, observation sheet, and field note. This research findings found that Think-Pair-Share technique could improve the students’ ability in writing recount texts. Students’ mean score improved from 54.46 in pre-test to 65.14 in post-test 1, and to 77.64 in post-test 2. It is in line with the activeness of students that improved from 46.08% in cycle 1 to 86.26% in cycle 2. Think-Pair-Share technique helped students in writing the recount texts. It analyzes each part of generic structure of recount text. Think-Pair-Share strategy could motivate the students during teaching and learning process. This research recommended that teachers to use Think-Pair-Share to find out the different effect after using this cooperative learning technique than a conventional technique.Key words: Think Pair Share Technique, writing ability, recount text